Quick Wilt Disease Of Pepper Symptomatological Studies On The Quick Wilt Disease Of Pepper - Mammootty KP (Department of Plant Pathology, College of Horticulture, 1978)
The present study on the quick wilt disease of pepper caused by Phytophthora palmivora (Butler) Butler was conducted at the Pepper Research Station, Vellanikkara using Panniyoor-1 pepper variety. The objectives of the investigations were to study the symptoms of the disease and to find out suitable control measures using fungicides. The first visible symptom on leaf, stem and root was noticed 24 to 48 hours; two to five days and 24 to 48 hours respectively after inoculation, depending on the maturity of the plant part. A fully developed lesion had a dark brown hononecrotic centre and plesionecrotic boarder surrounded by yellow halo. The yellow halo was not noticed during prolonged wet and humid conditions. Under these conditions lesions was uniformly brown in colour. Zonations were noticed during the alternate wet and dry conditions. On the stem, branches and roots symptom usually developed as a uniformly brown and dark coloured lesions. Pathogen entered mainly though lower surface of the leaf. After infection, defoliation took place within five to ten days. Development of flaccidity, drooping and defoliation of the leaves were the marked symptoms during the progress of disease when the stem, branches or roots were infected. All the fungicides tested checked the growth of the fungus in vitro for a period of three days. The fungicides when sprayed or drenched two hours before inoculation completely checked the disease. However, there was mild infection on plant where Dithane M-45 was used for drenching the soil. As the interval between the fungicidal spray and inoculation prolonged there was progressive reduction in the control of the disease. None of the fungicides was able to eradicate completely the established pathogen on leaves. When fungicides were applied one day after inoculation there was complete control of the disease on stem. While the control was not complete when it was applied two days after inoculation. All the fungicides except Dithane M-45 completely checked the development of the disease when they were drenched in soil.